Selected Factors Influencing China's Palm Oil Import Demand from Malaysia - Ahmad, Mohammad Yusof; Wong, Kelly Kai Seng; Kamarulzaman, Nitty Hirawaty (Universitas Muhammadiyah Yogyakarta, 2022)
The export of palm oil from Malaysia to China has declined since 2013, although the Malaysian Ringgit has depreciated. The Malaysian palm oil market has also struggled against the Indonesian palm oil and soy oil in China. Hence, this study aimed to identify the significant factors influencing China's demand for Malaysian palm oil by adopting the Auto-Regressive Distributed Lag (ARDL) analysis. The finding revealed that the currency rate of exchange, the foreign trade price of Malaysian palm oil to China, and the international soy oil price significantly influence Malaysian palm oil demand in China. Nevertheless, China's real GDP per capita showed a positive and significant influence only in the long run. The demand for Malaysian palm oil in China was not significantly impacted by the palm oil price offered by Indonesia, neither in the long run nor short run. Thus, the authorities related to this industry need to strategize the stock management system to control the price and currency stabilization to maintain its competitive power.